Effect of streamwise spacing on the sound generated by flow through two square cylinders in tandem arrangement - Manshoor, Bukhari; Zaman, Izzuddin; Khalid, Amir; Ghazali, M.F.; Khandelwal, Manish K. (WARSE, 2020)
The sound generated by the flow past two square cylinder in tandem arrangements was investigated by direct solution of two dimensiona1, unsteady, compressible Navier-Stokes equation. The main objective of the investigation is to study the effect of the spacing between two square cylinders on the generation and propagation mechanism of the sound. Since the sound pressure is very small compared to normal pressure and other parameters, high order computational scheme was use to captured the pressure fluctuations. Besides that, filtering is em-ployed to eliminate the high frequency part caused by nonlinearity of the governing equations. 4th order Runge-Kutta method was employed for time marching and for the boundary condition, adiabatic and non-slip conditions are imposed on the surface of the square cylinders. Present results for near-field flow features are in good agreement with the experimental results by previous researchers though the Reynolds number ranges examined are different. From the results, it shows that tandem arrangement of two cylinders with a small spacing may be useful for a passive control to reduce the generated sound since the larger spacing (L/D > 4), the shear layer separated from the upstream cylinder rolls up and forms vortices in front of the downstream cylinder. The results also showed that body-vortex interaction enhances the amplitude of the generated sound significantly.